SCAPS-1D Numerical Optimization of ZnO:Al/PCBM/CsSnI₃/MoO₃ Perovskite Solar Cells - Zineb Ibtissem Gouchida; Yazid Benbouzid; Mostefa Maache; Zehor Allam (International Journal of Computational and Experimental Science and Engineering, 2026)
A numerical optimization of lead-free ZnO:Al/PCBM/CsSnI₃/MoO₃ perovskite solar cells is performed using the SCAPS-1D simulator. The effects of absorber and transport layer thickness, doping concentration, defect density, series and shunt resistances, and operating temperature on device performance are systematically investigated. The results show that the CsSnI₃ absorber thickness and defect density dominate recombination losses and efficiency, while the PCBM layer exhibits strong defect tolerance. Optimized absorber thickness (1.2 μm) and acceptor doping (1019 cm-3) significantly enhance charge collection and fill factor. Series resistance strongly degrades performance, whereas high shunt resistance is essential for achieving high open-circuit voltage. Under optimized conditions, a maximum power conversion efficiency of 25.39% is achieved, representing a theoretical upper limit for CsSnI₃-based single-junction solar cells. The study provides clear guidelines for defect passivation and interface engineering in lead-free perovskite photovoltaics.